HAK ASASI MANUSIA DALAM PERSPEKTIF ISLAM DAN MAQASHID AL-SYARI’AH - Mufarrihul Hazin; Nur Wedia Devi Rahmawati; Muwafiqus Shobri (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2021)
The most basic right given by Allah SWT to mankind that is attached to him is a basic right. In the of Islamic teachings, the al-Qur'an and As-Sunnah focuses on the rights of neglected people. Intruth, with the presence of Islam one of the objectives is to lift the dignity of mankind and provide teaching with friendly teachings. Previously in the time before Islam came, people were treated unnaturally and employed arbitrarily without paying attention to aspects of human values. Therefore, this paper to explore the nature of Human Rights Islamic perspective with its principles and maqashid al-shari'ah.